2000
DOI: 10.1021/jp0031045
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Properties of Supercritical C14TEMPO Monolayers at the Air/Water Interface

Abstract: Monolayers of 4-tetradecaneamido-2,2,6,6-tetramethyl-1-piperidinyloxy (C 14 TEMPO) were investigated at the air/water interface. Pressure-area diagrams and Brewster angle microscopy provided evidence of supercritical state of this monolayer at temperatures as low as 2°C. The supercritical character of C 14 TEMPO Langmuir monolayers allowed the 2-D voltammetric measurements of its lateral diffusion constant, D, to be extended into a previously inaccessible region of low surface densities with mean molecular are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…These are separated by a bulky, lipophilic piperidine ring with four side methyl groups. These structural features are critical to the observed phase behavior reported recently and discussed in this report . Specifically, we postulate that in the high-pressure region, these compounds assume a vertical orientation of the TEMPO headgroup, minimizing their cross sectional area (see Figure ).…”
Section: Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…These are separated by a bulky, lipophilic piperidine ring with four side methyl groups. These structural features are critical to the observed phase behavior reported recently and discussed in this report . Specifically, we postulate that in the high-pressure region, these compounds assume a vertical orientation of the TEMPO headgroup, minimizing their cross sectional area (see Figure ).…”
Section: Resultsmentioning
confidence: 57%
“…2D Electrochemistry. In our previous paper, we reported a discontinuity in the 2D voltammetry of tetradecane ferroceneketone (C 14 Fc) upon slow expansion of its monolayer on the water surface . Our observations indicated that the 2D voltammetric “line” microelectrode which resides by self-positioning exactly in the plane of the air/water interface functions as a nucleating site for the monolayer gas phase.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations